Investigative Journalism and Risk Management Frameworks: Strategies for Protecting Journalists in High-Risk Environments of the Niger Delta - Timothy Ekeledirichukwu Onyejelem (Budapest International Research and Critics University, 2025)
Investigative journalism is a cornerstone of accountability, transparency, and democratic health, yet its practitioners often venture into perilous territories. In regions like the Niger Delta, known for its volatile mix of resource-driven conflicts, widespread environmental degradation, organised crime, corruption, and political instability, journalists face a particularly acute and complex web of threats. This paper sets out to explore the critical intersection of investigative journalism and risk management, with a keen focus on practical strategies for protecting journalists operating in such hostile environments as the Niger Delta. Specifically, it aims to: Examine the multifaceted risks of physical, digital, legal, and psychological confronting investigative journalists in high-risk zones, particularly within the Niger Delta; and identify and analyse both individual coping mechanisms and institutional support frameworks designed to mitigate these dangers in the context of the region's specific threats. Utilising philosophies from media safety studies, risk communication theories, and research on press freedom, this study offers a comprehensive framework for understanding how journalists perceive, communicate, and manage hazards. These theoretical frameworks elucidate the systemic challenges encountered by journalists and the strategic measures required to operate in contexts where the quest for truth frequently results in significant consequences, especially in the context of persistent environmental and political instability characteristic of the Niger Delta, This paper employs a comprehensive review of recent academic literature, empirical studies, and real-world case studies predominantly focused on investigative journalism in high-risk zones, with a particular emphasis on the African context, including the Niger Delta. This approach allows for the identification of recurring patterns of threats, effective mitigation strategies, and emerging best practices in journalist protection, while also considering the unique digital media ecosystem challenges faced by journalists in the region, The findings highlight that journalists in the Niger Delta and similar high-risk areas grapple with pervasive threats ranging from physical violence, arbitrary detention, and kidnapping to sophisticated digital surveillance and severe psychological stress. These threats are often exacerbated by the region’s specific challenges, including militancy, oil theft, and the activities of powerful economic and political actors. Effective protection strategies are found to be multifaceted, encompassing individual preparedness (e.g., advanced safety training, encrypted communication, meticulous source protection) and robust institutional support (e.g., strong press unions, clear organisational safety protocols, international solidarity, and legal aid).